1990
DOI: 10.1002/1097-4679(199009)46:5<600::aid-jclp2270460509>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

What does the Keane et al. PTSD scale for the MMPI measure?

Abstract: The correlations of the Keane, Malloy, and Fairbank (1984) MMPI PTSD scale with DSM‐III‐based post‐traumatic stress disorder symptom, section, and factor score ratings, and with combat history, were studied to determine what aspects of the disturbance it measures (N = 61). The scale's correlations with the various symptom criteria were both substantial and strikingly consistent. However, its relationships with trauma history measures were modest and frequently nonsignificant. The data suggest that the scale is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
4
14
0
2
Order By: Relevance
“…Consistent with previous investigations (Watson et al, 1990), these findings suggest the scores on the PK Scale may only be weakly related to the overall level of trauma exposure. However, the present findings should not be interpreted as evidence of no relationship between prior abuse and PTSD symptomatology in battered women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous investigations (Watson et al, 1990), these findings suggest the scores on the PK Scale may only be weakly related to the overall level of trauma exposure. However, the present findings should not be interpreted as evidence of no relationship between prior abuse and PTSD symptomatology in battered women.…”
Section: Discussionsupporting
confidence: 89%
“…While more moderate classification rates for PTSD have been found, previous research has shown the PK Scale to be a valid and clinically useful measure of PTSD in combat veterans (Lyons & Keane, 1992;Watson, Juba, Anderson, & Manifold, 1990). To date, only one study has evaluated the validity of the PK Scale against DSM-III-R criteria (MA, 1987) for PTSD in noncombat, trauma victims.…”
mentioning
confidence: 99%
“…Although the MCMI-I1 has gained its widest recognition as an instrument useful for evaluating personality disorders, it also has potential utility in the assessment of malingering (Millon, 1987;Streiner & Miller, 1989;Wetzler & Marlowe, 1990;Widiger, 1985). Two scales of particular interest on the MCMI-I1 are the DIS and DEB (Bagby et al, 1990).…”
Section: Mcmz-ii Scalesmentioning
confidence: 99%
“…Ove studije su nama posebno zanimljive pošto će u ovom radu biti ispitivana ekvivalencija naše forme MMPI-202. Lambert i saradnici (Lambert, Andrews, Rylee, & Skinner, 1987), Schuldberg (1988), te Watson i saradnici (Watson, Juba, Anderson, & Manifold, 1990), našli su samo neznatne razlike između računarski podržanih i klasičnih verzija testa. Korelacije pojedinačnih skala između dve različite forme kretale su se u rasponu .68-.94.…”
Section: Istraživanja Ekvivalencije Računarski Podržanih I Klasičnih unclassified
“…U najvećem broju slučajeva ne razlikuju se drastično u zavisnosti od toga da li je između testa i retesta dolazilo do promene modaliteta testiranja. Ovi nalazi su u skladu sa ranije navedenim nalazima Lamberta i saradnika (Lambert et al, 1987), Schuldberga (Schuldberg, 1988) i Watsona i saradnika (Watson et al, 1990).…”
Section: Diskusijaunclassified